2016
DOI: 10.4103/2231-0762.189745
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of micronuclei frequency in individuals with a habit of tobacco by means of exfoliated oral buccal cells

Abstract: Aims and Objectives:To study the genotoxic effects of tobacco on the exfoliated buccal epithelial cells in patients with oral precancerous lesions (OPLs) and Patients with tobacco habit but without oral precancerous lesion(habit controls) by using micronucleus assay as well as the quantification and detection of the biomarkers in these premalignant lesions which will be helpful in finding those patients who are at higher risk for malignant transformation.Materials and Methods:Forty samples were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…These findings are biologically coherent and are compatible with the literature, in which some authors also verified in their respective studies a direct relationship between the frequency of MN and tobacco consumption. 21,22 Like Namala et al, in the present study we verified that cells of the control group occasionally presented MN, but MN frequency was statistically higher in the smoker group, confirming that tobacco consumption increases MN frequency. 5 This represents the cytogenetic damage caused by smoking as being quite significant.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are biologically coherent and are compatible with the literature, in which some authors also verified in their respective studies a direct relationship between the frequency of MN and tobacco consumption. 21,22 Like Namala et al, in the present study we verified that cells of the control group occasionally presented MN, but MN frequency was statistically higher in the smoker group, confirming that tobacco consumption increases MN frequency. 5 This represents the cytogenetic damage caused by smoking as being quite significant.…”
Section: Discussionsupporting
confidence: 88%
“…The duration of addiction of the chewing habit in the present study of 50 individuals was in average of 1-20 years, which is in accordance with the study done by Jyoti et al 13 In present study, the tobacco chewers and betel quid chewers have shown a greater number of MN as compared to the healthy control group. This finding relates to that of Sellappa et al, 14 Palaskar and Jindal, 15 Joshi et al, 16 Dosi et al, 17 and Sharma et al 4 We also observed variations in the frequency of micronucleated cells in the control group, which may be probably due to the different food habits within the population group as individuals are exposed to various chemicals in their daily life, which was the reason for the variable levels of micronucleated cells. 13 On the other hand, Bansal et al 18 and Ozkul et al 19 in their work showed a higher level of the mean number of MN in smokeless tobacco users as compared with smokers, thus indicating higher carcinogenic potential of smokeless tobacco.…”
Section: As Followssupporting
confidence: 86%
“…There is a three-fold higher MN rate per cell in the group of tobacco chewers and tobacco chewers with lesion patients than in the control group, and a number of studies have shown a gradual increase in MN frequency from normal to precancerous to cancerous lesions as done by Palaskar and Jindal, 15 Jyoti et al, 13 Caplash et al, 11 and Dosi et al 17 Cytobrushes appear to be most effective for collecting large numbers of cells, and the high expense makes them less feasible for routine purposes. So, we preferred the use of a wooden spatula.…”
Section: As Followsmentioning
confidence: 91%
“…These structures have similar appearance to those structures which can be observed in the cellular nuclei during of interphase. 4,5 Therefore, in the present study we aimed to evaluate the genotoxic effects of tobacco chewing by means of micronucleus assay in exfoliated cells of buccal mucosa.…”
Section: Introductionmentioning
confidence: 99%